ESR1 mutations: Moving towards guiding treatment decision-making in metastatic breast cancer patients. (January 2017) - Angus, Lindsay; Beije, Nick; Jager, Agnes; Martens, John W.M.; Sleijfer, Stefan
Highlights: Mutations in the ligand binding domain of ESR1 lead to ER constitutive activity. ESR1 mutations are associated with acquired endocrine resistance. Cell-free DNA is a good substrate for ESR1 mutation detection. ESR1 mutation analyses have great potential for clinical decision-making. Abstract: Mutations in the gene coding for the estrogen receptor (ER), ESR1, have been associated with acquired endocrine resistance in patients with ER-positive metastatic breast cancer (MBC). Functional studies revealed that these ESR1 mutations lead to constitutive activity of the ER, meaning that the receptor is active in absence of its ligand estrogen, conferring resistance against several endocrine agents. While recent clinical studies reported that the occurrence of ESR1 mutations is rare in primary breast cancer tumors, these mutations are more frequently observed in metastatic tissue and circulating cell-free DNA of MBC patients pretreated with endocrine therapy. Given the assumed impact that the presence of ESR1 mutations has on outcome to endocrine therapy, assessing ESR1 mutations in MBC patients is likely to be of significant interest to further individualize treatment for MBC patients. Here, ESR1 mutation detection methods and the most relevant pre-clinical and clinical studies on ESR1 mutations regarding endocrine resistance are reviewed, with particular interest in the ultimate goal of guiding treatment decision-making based on ESR1 mutations.